The Relationship between Motivation and Gamification in Improving Foreign Language Speaking (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Motivation and gamification are two key factors that play a significant role in improving foreign language speaking skills. The relationship between these two concepts is complex and multifaceted, as they both have a direct impact on an individual's willingness to engage in language learning activities and their ability to retain and apply new language skills. In this article, we will explore the relationship between motivation and gamification in the context of improving foreign language speaking skills, and discuss how these two factors can work together to enhance language learning outcomes.